A reliable A-MSDU frame aggregation scheme in 802.11n wireless networks - Saif, Anwar (Elsevier, 2013)

(untitled)
IEEE 802.11n standard is introduced to enhance the throughput to more than 100Mbps at the MAC service access point. This high throughput is achieved through several enhancements at the physical and MAC layers. Frame aggregation is a key enhancement at the MAC later in which multiple frames are concatenated and then sent in one channel access. In error free channels the 802.11n MAC service data unit aggregation (A-MSDU) performs better than the MAC protocol data unit aggregation (A-MPDU)due to its smaller headers. However, the performance of A-MSDU at erroneous channels is poor due to lack of sub-frames integrity check. In this paper, we proposed an A-MSDU frame aggregation with sub-frame integrity check and retransmission at the MSDU level without altering the original MAC frames header structure. The results show that the proposed scheme improves the system performance in terms of throughput and delay even under highly erroneous channels.